Electrochemical Determination of Copper(II) in Water Samples Using a Novel Ion-Selective Electrode Based on a Graphite Oxide-Imprinted Polymer Composite - Topcu, Cihan; Lacin, Gamze; Yilmaz, Vedat; Coldur, Fatih; Caglar, Bulent; Cubuk, Osman; Isildak, Ibrahim (TAYLOR & FRANCIS INC, 2018)
A novel copper(II)-selective electrode based on graphite oxide/imprinted polymer composite was developed for the electrochemical monitoring of copper(II) (Cu2+) ions. The electrode exhibited highly selective potentiometric response to Cu2+ with respect to common alkaline, alkaline earth and heavy metal cations. The composite composition studies indicated that the most suitable composite composition performing the most promising potentiometric properties was 20.0% ionophore (Cu2+-ion imprinted polymer), 10.0% paraffin oil, 5.0% multiwalled carbon nanotubes, and 65.0% graphite oxide. The fabricated electrode exhibited a linear response to Cu2+ over the concentration range of 1.0 x 10(-6)-1.0 x 10(-1) M (correlation coefficient of 0.9998) with a sensitivity of 26.1 +/- 0.9 mV decade(-1). The detection limit of the fabricated electrode was determined to be 4.0 x 10(-7) M. The electrode worked well in the pH range of 4.0-8.0. The electrode had stable, reversible and fast potentiometric response (3 s). In addition, the electrode had a lifetime of more than 1 year. The analytical applications of the proposed electrode were performed using as an indicator electrode for the potentiometric titration of Cu2+ with ethylene diamine tetraacetic acid solution and for the determination of Cu2+ of spiked river, dam, and tap water samples. The obtained results for potentiometric titration and water samples were satisfactory.
Keywords: Copper(II) determination; copper(II)-selective electrode; ion-imprinted polymer; potentiometry; water analysis; SYNTHESIZED SCHIFF-BASE; SPECTROPHOTOMETRIC DETERMINATION; POTENTIOMETRIC SENSOR; MERCURY IONS; MEMBRANE; IONOPHORE; ZINC; MANGANESE; MATRICES; Chemistry